A63 TRANSPLANTATION OF A LIVER ALLOGRAFT FROM A HEPATITIS C VIRUS (HCV) SEROPOSITIVE DONOR WITH PREVIOUS SUSTAINED VIROLOGIC RESPONSE TO AN UNINFECTED RECIPIENT SUFFERING STEROID REFRACTORY ACUTE GRAFT REJECTION WITH NO EVIDENCE OF HCV TRANSMISSION. (1st March 2018) - Mitchell, R A; Hussaini, T; Yau, A; Krajden, M; Wright, A J; Scudamore, C; Marquez, V; Erb, Z; Yoshida, E M
Abstract: Background: The goal of treating chronic hepatitis C virus (HCV) infection is sustained virologic response (SVR). There is concern that despite achieving SVR, replication-competent HCV may be sequestered at low levels within the liver and could theoretically reactivate with immunosuppression. Aims: We report transplantation of a HCV seropositive liver donor, who achieved SVR, into a seronegative patient without HCV reactivation despite profound immunosuppression. Methods: Retrospective chart review. Results: We present a 21-year-old male who was HCV seronegative and received a liver transplant from a donor who had been treated for HCV and achieved SVR. The liver recipient, despite developing severe acute graft rejection and undergoing intense immunosuppression with T-cell depleting antibodies, did not become HCV RNA positive with a follow up period of 8 months. The recipient was HCV seronegative before transplant, but became HCV seropositive immediately post-transplant. The antibodies were undetectable after 97 days, in keeping with a passive antibody transmission or B lymphocyte transmission with the graft. Conclusions: To the best of our knowledge, this is the first reported case of an HCV seropositive liver allograft transplanted into a HCV negative recipient. This case, therefore, is an encouraging and novel step in liver transplantation, and demonstrates that SVR may be closer to a true "cure" of HCV in the donor population and that, even in circumstances of very potent immunosuppression in the recipient, this SVR is sustained. To our knowledge, this case also contains the first documented example of an HCV antibody decay phenomenon in the recipient post-liver organ transplant. Funding Agencies: None